Structural and optical properties of Er3 +-Yb3 + codoped multicomposition TeO2-ZnO-PbO-TiO2-Na2O glass - Omar Baki, Sharudin; Tan, L. S.; Kan, C. S.; Mohamed Kamari, Halimah; Muhammad Noor, Ahmad Shukri; Mahdi, Mohd Adzir (Elsevier, 2013)
We investigate the structural and spectroscopic properties of multicomposition Er3 +-Yb3 + codoped TeO2-ZnO-PbO-TiO2-Na2O glass. Both structural and thermal studies have been performed via X-ray diffraction and differential scanning calorimetry respectively in order to verify its glassy nature. The Raman spectroscopy has revealed the glass network consists of [TeO4], [TeO3 + 1] and [TeO3] groups as basic structural units. Optical absorption measurements have been carried out and analyzed by Judd–Ofelt and McCumber theories where important spectroscopic parameters such as intensity parameters Ωt (t = 2, 4, 6) transition probabilities, and stimulated emission cross section at 1.5 μm are calculated. Broad near-infrared emission at 1564 with full width at half maximum around 70 nm were obtained under 980 nm laser excitation.